Bi-cultural competence and academic resilience among immigrants - Vargas-Reighley, Rosalva Vega, 1961- (New Americans (LFB Scholarly Publishing LLC), 2005)
"The New Americans explores recent immigration and related changes in American society from the perspectives of sociology, anthropology, education, history, political science, psychology, economics, and law. Together the books help us to understand how immigration is changing the United States."--Jacket.